Educational Trajectories of Parents as a Factor of Reproductive Behavior on the Example of the Republic of Tatarstan (2013-2022) - Ch. I. Ildarhanova; G. N. Ershova (Высшее образование в России)
The aim of the study was to assess the impact of parents’ educational trajectories on reproductive behavior using the example of the Republic of Tatarstan for 2013-2022. The hypothesis of the study: the increase in the educational level of parents in 2013-2022 led to delayed parenthood, an increase in the average age of parents at the birth of first-born children, a decrease in boarding periods due to the effect of catching up growth; the proportion of children born to parents with high professional qualifications increases. The main methods were a cross-sectional analysis of data from sociological studies on the generative behavior of men and women in the Republic of Tatarstan, a statistical analysis of time series of indicators of age and education of parents. As a result of the analysis of sociological research data, differences in the number of available and desired children in the family were revealed, depending on the level of education of the parents and the territory of their residence. For 2013-2022 The share of births to mothers with higher and incomplete higher education on average in the Russian Federation increased from a third of all births to half, and in the Republic of Tatarstan – from 50% to 60%. Parents receiving higher education leads to a shift in the birth calendar: an increase in the protonatal period, while the hypothesis of a reduction in the periods between the births of the first and second children, depending on the level of education of the parents, has not been confirmed. The period between the first and second births ranges from 2 to 6 years, for women with higher education and an academic degree, it is slightly longer. The novelty of the work lies in assessing the impact of parental education on the desired number of children, determining the average age of the father at the birth of the first child and the boarding periods, their assessment in the context of the city-village based on the results of sociological studies on the generative behavior of men and women in the Republic of Tatarstan.